(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Infertility is a global health issue affecting 8 to 12% of couples worldwide. The objective was to study the prevalence and socio-demographic profile of infertility in the study population. Aim and Objective: To study the socio-demographic profile in couples seeking treatment for infertility Methodology: It was a hospital based prospective observational study that included all couples attending the out-patient clinic of Obstetrics and Gynaecology department at Santosh medical college and hospital, Ghaziabad. The study was conducted over a period 18 months from January 2019-June 2020. Out of a total of 193 couples who were recruited and investigated, 11 were lost to follow up and 10 patients didn’t get fully investigated so the remaining 172 couples who satisfied the inclusion criteria were enrolled in the study. Result: Pathologies such endometriosis, genital tuberculosis, and pelvic inflammatory disease are among the tubal causes. In our study, 36.36% of the cases had PCOS. Fibroids, endometrial polyps, and uterine abnormalities are uterine factors. Conclusion: The proportion of primary infertility in our study was higher than the proportion of secondary infertility. Pelvic inflammatory diseases, tubal factors, abortion, and ovulatory dysfunction were the most prevalent causes of female infertility.